Electron Microscopic Changes of Rabbit Retina after Chromovitrectomy Using Combined Dyes (Experimental Study) - B. M. Aznabaev; Z. R. Yanbukhtina; T. R. Mukhamadeev; T. I. Dibaev; G. R. Shakirova (Oftalʹmologiâ)
Purpose: to evaluate on experimental model electron-microscopic changes of rabbit retina after staining of the posterior eye segmentwith combined dyes based on Trypan blue and Brilliant blue G for the assessment of their safety. Methods. The study was performed onChinchilla breed rabbits. Combined dyes based on Trypan blue and Brilliant blue were used: MembraneBlue-Dual (DORC, Netherlands)and “Staining solution for ophthalmic surgery” (JCS “Optimedservis”, Russia). Standard three-port vitrectomy technique was used. After vitreous removal dyes were injected in vitreous cavity and exposed for 10 seconds and then removed. The vitreous cavity was filled by a balanced salt solution. An electron-microscopic evaluation was performed on 5, 14 and 30 days after surgery. Eyes were enucleated in 20 minutes after animal was killed by air embolization. Intact eyes were used as a control, all samples were prepared in same сonditions. The damage of the retina architectonics and the presence of intracellular inclusions were evaluated. Results. The staged character of pathomorphological changes was revealed. On the 5th day moderate edema and hydropic dystrophy of neurons were registered. On the 14th day, there was no negative dynamics. On day 30, the signs of edema and dystrophy of neurons practically disappeared, which may indicate a fundamental reversibility of the registered changes. Conclusion. Investigated dyes for staining intraocular structures based on Trypan blue and Brilliant blue did not cause significant histomorphological changes and toxic effects on retinal cell structures. Detected electron microscopic changes were insignificant, had reversible character and could be mostly caused by a surgical injury.